Types of derivational affixes in new idea magazine: a morphological analysis - Dwiyanti, Ni Kadek Chandra; Maharani , Putu Devi; Winartha, IB Gde Nova (Journal of Language and Applied Linguistics, 2022)
This study was aimed to identify the derivational affixes that can be found in “New Idea”magazine. Specifically, this study was focused on analyzing the types and the process of derivational affixes that were found in the data source. This study used qualitative descriptive method to analyze the data. The data were analyzed based on the theory proposed by Katamba (1993) to solve the problem which about the types of derivational affixes. Theory that proposed by Rochelle Lieber (2009) was used to solve the problem about the morphological process of derivational affixes. This study found 427 data that contains derivational affixes. Derivational prefixes were found in 52 data with percentage 12% such as prefix in-, un-, dis- , re-, ex-, en-, and pre-. Then, derivational suffixes were found in 375 data with percentage 88% such as suffix –hood, -ship, -ness, -ity, -ment, -less, -ful, -ic, -al, -er, -ly, -ion, -ish, -ing and –ed. This study concluded that derivational suffix –ly was the most dominant type of derivational affixes that found in“New Idea”magazine.